No Price for Grace: Canonical Reflections on Mass Offerings and the Poor - Galed, Daniel Ortega (Universitas Sanata Dharma, 2026)
In the evolving context of how the Church administers the sacraments, a profound question arises again regarding the practice of Mass offerings, especially in light of the decree issued by the Dicastery for the Clergy in April 2025. This paper will focus on cc. 848 and 945 §2, which emphasize justice and generosity in accepting Mass intentions, especially from the poor. How are we to respond pastorally to those who truly cannot make an offering? This question touches the core of the priestly vocation today: to embody a Church that stands with the marginalized, while reaffirming the identity of the priest as a servant of mercy, not merely a manager of rites. In the modern pastoral context, where poverty may change in form but never truly disappears, this issue presents both an urgent challenge and an invitation to remain faithful in serving Christ present in the poor.